Bitcoin's Position in Indonesian Currency Law - Eduardus Robert Arminanto; Kukuh Ari Firmansyah (Universitas Negeri Semarang, 2022)
The influence of technology and developing information is indeed extraordinary on human life. Economic development is also inseparable from the growing technology, for example in transaction procedures in a matter. Bitcoin came up with a new innovation in the form of a cryptocurrency that uses a payment network from user to user. Crypto has become a phenomenon nowadays. Based on the results of the Global Web Index Survey, 10% of internet users in Indonesia already own digital currencies, it can be said that Indonesia is ranked 5th most crypto users in the world. Crypto or can be called crytocurrency has a fairly high risk. Then kirpto has a change in value that is only enthusiasm at any time. Krip toalso has a lack of regulation and still leaves legality issues. This research was conducted to determine the existence of bitcoin trading to the national economy. The use of bitcoin over time is increasing in Indonesia. For this reason, before the use of bitcoin is increasing, we must understand the influence and impact of bitcoin trading on the national economy. Only nine countries have legalized bitcoin, it is questionable why many countries have not legalized bitcoin. This study aims to find out how bitcoin trading conditions in Indonesia. The results of this journal will discuss the effect of bitcoin trading on the national economy even though in Indonesia it is prohibited and recognized as legal tender. This can be viewed from several factors such as from the nominal side of bitcoin which is considered excessive, especially in the picture of the economic crisis.